Sponge zirconium-based composite material with low hydrogen embrittlement and high toughness and preparation method thereof
Through the in-situ self-generating and microstructure optimization of nano ZrC, the shortcomings of sponge zirconium-based composite materials in low hydrogen embrittlement and high toughness properties are solved, and the stable service and high comprehensive performance of the materials in extreme environments are achieved.
Patent Information
- Application Number
- CN202510357212.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-25
AI Technical Summary
The existing sponge zirconium-based composite materials have shortcomings in low hydrogen embrittlement and high toughness properties, and it is difficult to serve for a long time in extreme environments, and traditional methods have failed to effectively inhibit the expansion of hydrogen-induced cracks.
Through the synergistic effects of nano ZrC in situ self-generation, mechanical alloying, high-temperature densification, multi-stage temperature rolling and partition annealing, the microstructure of the material is optimized, gradient grain boundary distribution is formed, and the material's anti-hydrobrittleness ability and toughness are improved.
The low hydrogen embrittlement and high toughness of sponge zirconium-based composite materials have been achieved, and the defects of the traditional methods that are prone to brittlement in high temperature and high hydrogen environments have been overcome, and the comprehensive performance and service stability of the material have been improved.
Smart Images

Figure CN119859764A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of zirconium-based composite materials, and in particular to a low-hydrogen embrittlement and high-toughness sponge zirconium-based composite material and a preparation method thereof. Background Art
[0002] Zirconium sponge-based composite materials have a wide range of applications in the nuclear industry, high-end aerospace, and corrosion resistance fields. Especially in nuclear fuel cladding, nuclear reactor structural parts, and high-temperature corrosion-resistant alloys, zirconium sponge has become a key material due to its low thermal neutron absorption cross section, excellent corrosion resistance, and high-temperature stability. However, with the rapid development of nuclear industry and aerospace technology, the service environment of materials has become increasingly harsh. For example, long-term exposure to high temperature, high pressure, strong irradiation, and hydrogenated environments has significantly increased the risk of hydrogen embrittlement of materials, and at the same time, higher requirements are placed on the mechanical properties, toughness, and micro-stability of materials. In a nuclear reactor environment, hydrogen atoms are easy to diffuse and aggregate inside zirconium-based materials, resulting in phase boundary debonding, embrittlement, and strength loss, which seriously affects the reliability and service life of the material. Therefore, while ensuring the excellent corrosion resistance of the material, improving its ability to resist hydrogen embrittlement and optimizing the microstructure to enhance toughness have become important research directions in the current field of materials science and engineering. In response to this demand, strategies such as nano-enhancement mechanism, grain boundary structure optimization and gradient organization regulation have become key means to improve the comprehensive performance of zirconium-based composites. They can effectively alleviate hydrogen-induced cracking, improve the toughness and service stability of materials, thereby promoting the application expansion of such materials in complex environments and improving the safety and sustainability of nuclear energy and aerospace technology.
[0003] Although a large number of studies have been devoted to improving the hydrogen embrittlement problem of zirconium-based materials, there are still major technical bottlenecks. For example, the Chinese patent with publication number CN113201666A discloses zirconium alloys for fuel assemblies and their manufacturing methods, as well as cladding tubes for fuel assemblies. The hydrogen resistance is improved by microalloying, but it still faces the problem of high hydrogen embrittlement sensitivity and is difficult to serve for a long time in extreme environments. In addition, some researchers have introduced nanoparticles to improve strength and corrosion resistance, but due to the limited interfacial bonding between the ceramic phase and the metal matrix, the toughness of the material is reduced, making it difficult to balance high strength and high toughness. The existing technology is often accompanied by the side effect of reduced toughness while improving the hydrogen embrittlement resistance. The main reason is that traditional methods rely on solid solution strengthening, precipitation strengthening or surface coating methods, and fail to achieve grain boundary optimization and gradient control at the microstructure level, thereby failing to effectively inhibit the expansion of hydrogen-induced cracks. In addition, the uniformity of the distribution of the nano-enhanced phase, the phase boundary bonding force and the processing adaptability of the material are also key issues that currently restrict its practical application. Therefore, there is an urgent need to develop a sponge zirconium-based composite material with both low hydrogen embrittlement and high toughness, and to achieve stable service of the material in extreme environments through nanostructure design, gradient grain boundary regulation and optimized preparation process. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a low hydrogen embrittlement and high toughness sponge zirconium-based composite material and a preparation method thereof, so as to solve the problem that the current sponge zirconium-based composite material is insufficient in low hydrogen embrittlement and high toughness performance.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material comprises the following steps:
[0009] S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder;
[0010] S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano-ZrC dispersion-reinforced zirconium-based composite body is synthesized in situ;
[0011] S3. Surface mechanical grinding: The body of step S2 is subjected to surface mechanical grinding to form a surface nanocrystalline structure;
[0012] S4. Multi-stage warm rolling and grain boundary gradient control, the blank after step S3 is subjected to primary rolling and core rolling in sequence to obtain a gradient structure blank;
[0013] S5. Partition annealing to stabilize the gradient grain boundary: The green body treated in step S4 is subjected to surface annealing and core annealing in sequence to finally obtain a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness.
[0014] Furthermore, the detailed process of step S1 is: sponge zirconium powder and carbon black are mixed in a mass ratio of (97.0~98.0): (2.0~3.0), the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is (10.0~12.0):1, the rotation speed is 300~350rpm, and the ball milling time is 25~30h to obtain Zr-C composite powder.
[0015] The purpose of using S1 in the present invention is to achieve sufficient interface action on the basis of uniform mixing of sponge zirconium powder and nano carbon black through raw material pretreatment and mechanical alloying process, so as to obtain uniformly distributed Zr-C composite powder, and provide excellent precursor for subsequent densification and in-situ synthesis. Mechanical alloying can not only promote the diffusion and reaction between sponge zirconium powder and nano carbon black, but also introduce high-density lattice defects through high-energy ball milling process, improve the solid solubility of carbon atoms, and provide sufficient reaction activity for the subsequent in-situ self-generation of nano ZrC under hot isostatic pressing conditions. Using a high-energy planetary ball mill, mechanical alloying of sponge zirconium powder and carbon black under argon protection can not only effectively prevent powder oxidation and maintain the chemical purity of the material, but also control the microstructure of the powder through appropriate ball-to-material ratio, rotation speed and ball milling time, so as to ensure that a Zr-C composite powder with uniform particle size and good dispersibility is obtained.
[0016] Furthermore, the detailed process of step S2 is as follows: the Zr-C composite powder obtained in step S1 is loaded into a mild steel bag, and after evacuating to ≤5×10⁻³Pa, it is sealed by electron beam sealing welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1200~1250°C at a heating rate of 10~15°C / min, a pressure of 120~150MPa is applied, and the temperature and pressure are maintained for 180~240min. After the reaction is completed, it is cooled to room temperature at a cooling rate of 6.0~12.0°C / min.
[0017] The hot isostatic pressing densification and in-situ synthesis process of S2 of the present invention relies on the uniformity and activity of the composite powder obtained from S1, and promotes the dispersion distribution of nano ZrC in the zirconium matrix under high temperature and high pressure conditions, thereby effectively improving the strengthening effect of the material, so that it has good plasticity and toughness while maintaining high strength.
[0018] Furthermore, the detailed process of step S3 is: placing the green body obtained in step S2 in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 20-25 kHz, the amplitude to 50-60 μm, the processing time to 50-60 min, and adopting argon gas jet cooling during the treatment process. After the treatment is completed, argon gas jet cooling is adopted, and the cooling rate is 40-50 ° C / s.
[0019] The purpose of using S3 in the present invention is to introduce high-density grain boundaries and nano-scale grains in the surface layer of the material through surface mechanical grinding treatment to form a nanocrystalline structure, thereby optimizing the microstructure of the material and improving its hydrogen embrittlement resistance and mechanical properties. Although the nano ZrC dispersion-enhanced zirconium-based composite blank obtained by S2 has high strength and plastic toughness, its surface layer may still have a large grain size, which is not conducive to the hydrogen resistance and crack propagation resistance of the material in a complex service environment. Therefore, S3 uses ultrasonic surface mechanical grinding means to make the surface material undergo severe plastic deformation, promote grain refinement under high-frequency impact and shearing, and form a nanocrystalline structure on the surface. Using WC-Co grinding balls and processing under appropriate vibration frequency and amplitude conditions helps to increase the deformation energy storage per unit volume, so that the surface layer of the material undergoes dynamic recrystallization, while introducing high-density small-angle grain boundaries and dislocation twin structures, thereby effectively improving the toughness of the material. In addition, the formation of the nanocrystalline structure can also enhance the surface hardness of the material, improve its wear resistance and crack initiation resistance, and lay the foundation for subsequent grain boundary gradient regulation. During the whole process, the use of argon jet cooling not only helps to suppress overheating of the surface layer and maintain a uniform organizational state, but also avoids the adverse effects of high-temperature oxidation on material properties. The mechanical grinding process of S3 provides an optimized initial organization for the subsequent multi-stage warm rolling of S4, making the construction of the gradient structure more precise, and finally achieving the stabilization of the grain boundaries during the partition annealing process of S5, ensuring the service stability of the material in complex environments. Through the synergistic effect of S3 and the previous and subsequent processes, the present invention achieves a high degree of optimization of the surface organization while ensuring the overall strength of the material, thereby giving the material excellent comprehensive performance and meeting the application requirements of low hydrogen embrittlement and high toughness.
[0020] Furthermore, the detailed process of the initial rolling in step S4 is as follows: the surface of the billet treated in step S3 is induction heated to 650-700° C., and rolling is performed with a rolling force of 780-800 kN, a pass reduction of 15-20%, and 4-6 passes.
[0021] Furthermore, the detailed process of the core rolling in step S4 is: heating the entire billet after the initial rolling to 600-650° C., rolling with a rolling force of 250-300 kN, a pass reduction of 5.0-8.0%, and rolling in 4-6 passes.
[0022] The purpose of S4 of the present invention is to introduce a gradient grain structure into the material through a multi-stage warm rolling process, so that the microstructure of the surface layer, transition zone and core is gradually optimized to improve the mechanical properties and hydrogen embrittlement resistance of the material. The surface mechanical grinding of S3 has formed a nanocrystalline structure on the surface of the material, but the overall organization still needs to be further regulated to ensure that the grain distribution in different regions is reasonable, so as to take into account high strength, high toughness and excellent hydrogen resistance. Therefore, S4 first deforms and strengthens the surface of the blank at a temperature of 650~700℃ through initial rolling, so that the surface organization is further refined, and at the same time, the grain boundary evolution of the transition zone is promoted, the dislocation density is increased, and the overall uniformity of the material is enhanced. The use of appropriate rolling force and multi-pass rolling method can effectively control the degree of deformation and ensure that a reasonable grain boundary structure is formed in the surface layer and transition zone. Subsequently, the core rolling is carried out under relatively low temperature conditions to keep the overall organization uniform under a small deformation amount, while reducing the internal residual stress and preventing the material from cracking or excessive organization distortion. Through this gradient deformation mechanism, the surface of the material acquires an ultrafine grain structure, the transition zone forms a fine grain structure, and the core maintains a moderate equiaxed grain distribution, thereby optimizing the mechanical properties as a whole. The multi-stage warm rolling of S4 not only lays the organizational foundation for the partition annealing of S5, but also ensures the comprehensive performance of the final composite material, enabling it to have excellent service stability and resistance to hydrogen damage in complex environments.
[0023] Furthermore, the detailed process of the surface annealing in step S5 is: using laser selective heating, the heating power density is 4.0~5.0W / mm², the spot diameter is 2.0~4.0mm, the surface area is heated to 650~660℃, after keeping warm for 30~45min, argon gas injection cooling is used, and the cooling rate is 40~50℃ / s.
[0024] Furthermore, the detailed process of the core annealing in step S5 is: placing the blank in a resistance furnace, heating it to 480-490°C at a heating rate of 5.0-8.0°C / min, keeping it warm for 90-120 minutes, and then cooling it to room temperature at a cooling rate of 2.0-5.0°C / min.
[0025] The purpose of S5 of the present invention is to further stabilize the gradient microstructure of the material, optimize the grain boundary distribution, reduce the residual stress, and improve the comprehensive mechanical properties and hydrogen embrittlement resistance of the material through the partition annealing process. In the multi-stage warm rolling process of S4, the surface layer, transition zone and core of the material have formed a gradient grain structure, but due to the introduction of higher dislocation density and residual stress during the rolling process, it is necessary to regulate and control through a reasonable heat treatment process to ensure the microstructural stability and service performance of the material. To this end, the present invention adopts a combination of surface annealing and core annealing to achieve precise heat treatment of different areas. The surface annealing adopts a laser selective heating method, and is kept warm for a short time in the temperature range of 650~660℃, and argon jet cooling is used to ensure the stabilization of the surface organization, while avoiding abnormal grain growth, so that the surface still maintains a fine grain structure and improves its hydrogen embrittlement resistance. At the same time, the core annealing adopts a relatively low temperature overall heating method, and is kept warm for a long time at 480~490℃, so that the residual stress in the core can be effectively released, while promoting dislocation rearrangement and grain boundary migration, thereby optimizing the internal organization and improving the toughness and plasticity of the material. Through the precise control of the annealing temperature and cooling rate in different regions, the uniformity of the organization of the surface layer, transition zone and core and the stability of the gradient structure are ensured, so that the material has excellent toughness and hydrogen damage resistance while maintaining high strength. The S5 partition annealing process not only improves the gradient structure constructed by the aforementioned S3 surface mechanical grinding and S4 multi-stage warm rolling, but also ensures the long-term stability of the material in complex service environments, providing important support for the engineering application of low hydrogen embrittlement and high toughness sponge zirconium-based composite materials.
[0026] The present invention also discloses a low hydrogen embrittlement and high toughness zirconium sponge-based composite material, wherein the zirconium sponge-based composite material is obtained by the above-mentioned preparation method;
[0027] The sponge zirconium-based composite material is composed of nano ZrC and a Zr matrix;
[0028] The volume ratio of the nano ZrC to the Zr matrix is (4.5-8.0): (92.0-95.5);
[0029] The average diameter of the nano ZrC is 10.0-60.0 nm;
[0030] The nano ZrC is produced in situ by in-situ self-generation of sponge zirconium powder and nano carbon black at high temperature;
[0031] The sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside;
[0032] The thickness of the surface region is 35-70 μm; the small-angle grain boundaries in the surface region account for 82.3-88.7%; the large-angle grain boundaries account for 11.7-15.9%; and the twin boundaries account for 0.4%-1.0%;
[0033] The thickness of the transition region is 50-150 μm; the small-angle grain boundaries in the transition region account for 25.7-34.7%; the large-angle grain boundaries account for 59.7-67.3%; and the twin boundaries account for 5.1-7.5%;
[0034] The small-angle grain boundaries in the core account for 6.5-10.5%, the large-angle grain boundaries account for 71.8-78.8%; and the twin boundaries account for 13.4-19.0%.
[0035] The present invention adopts the design of nano ZrC to strengthen the Zr matrix, which is mainly used to enhance the hydrogen embrittlement resistance and toughness of the sponge zirconium-based composite material. Through the dispersion strengthening effect of nano ZrC and the optimization of the gradient grain boundary structure, the high strength, high toughness and good service stability of the material are achieved. The volume fraction of nano ZrC is controlled within a reasonable range, and is formed by the in-situ reaction of sponge zirconium powder and nano carbon black at high temperature, so that the reinforcement phase is evenly distributed in the matrix, effectively improving the strengthening effect of the material, while avoiding the problem of insufficient interface bonding force that may be caused by the traditional external reinforcement phase. The microstructure of the material changes from the surface area, the transition area and the core area in sequence to form a gradient grain boundary distribution, so that the material has both high strength and good toughness in different areas, thereby improving the overall hydrogen embrittlement resistance. Because the surface area undergoes strong plastic deformation and dynamic recrystallization during the preparation process, its grains are further refined to form high-density small-angle grain boundaries, which helps to inhibit the diffusion and aggregation of hydrogen, reduce hydrogen embrittlement sensitivity, and improve the wear resistance and surface hardness of the material. The grain boundary structure in the transition area is reasonably distributed among small-angle grain boundaries, large-angle grain boundaries and twin boundaries, ensuring the balance between strength and toughness of the material, causing cracks to deflect during expansion, thereby improving fracture toughness. The core area is dominated by large-angle grain boundaries and a high proportion of twin boundaries. The presence of twin boundaries can effectively absorb deformation energy, improve the plastic toughness of the material, and reduce the risk of hydrogen-induced cracking. Through the synergistic effect of nano-ZrC reinforcement and gradient grain boundary regulation, the material has excellent toughness and hydrogen embrittlement resistance while maintaining high strength, meeting the service requirements in harsh environments and enhancing its application value in the nuclear industry and high corrosion resistance fields.
[0036] (3) Beneficial technical effects
[0037] The present invention realizes low hydrogen embrittlement and high toughness of sponge zirconium-based composite materials through the synergistic effects of in-situ self-generation of nano ZrC, mechanical alloying, high-temperature densification, multi-stage warm rolling and zone annealing. Compared with the prior art, the present invention optimizes the distribution of nano ZrC, improves the interface bonding force, avoids the inhomogeneity problem caused by the traditional external reinforcement phase, and improves the overall toughness through gradient grain boundary regulation, overcoming the defect of conventional zirconium alloys being easily brittle in high temperature and high hydrogen environments. The present invention can be widely used in high-end fields such as nuclear industry, aerospace, etc., to meet the needs of long-term service. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a microstructure interface morphology of the zirconium sponge-based composite material prepared in Example 1 of the present invention.
[0039] Figure 2 This is the electron backscatter diffraction pattern of the surface area prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0041] Example 1
[0042] A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material comprises the following steps:
[0043] S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder; the detailed process is: Sponge zirconium powder and carbon black are mixed in a mass ratio of 97.0:3.0, the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is 10.0:1, the rotation speed is 300rpm, and the ball milling time is 25h to obtain Zr-C composite powder.
[0044] S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano ZrC dispersion-reinforced zirconium-based composite material blank is synthesized in situ; the detailed process is as follows: the Zr-C composite powder obtained in step S1 is loaded into a soft steel bag, evacuated to ≤5×10⁻³Pa, and then sealed by electron beam welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1200°C at a heating rate of 10°C / min, a pressure of 120MPa is applied, and the temperature is maintained for 180min. After the reaction is completed, the temperature is cooled to room temperature at a cooling rate of 6.0°C / min.
[0045] S3. Surface mechanical grinding treatment: The green body of step S2 is subjected to surface mechanical grinding treatment to form a surface nanocrystalline structure; the detailed process is: the green body obtained in step S2 is placed in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 20kHz, the amplitude to 50μm, the processing time to 50min, and argon jet cooling during the treatment process. After the treatment is completed, argon jet cooling is used, and the cooling rate is 40℃ / s.
[0046] S4. Multi-stage warm rolling and grain boundary gradient control, the blank treated in step S3 is subjected to primary rolling and core rolling in sequence to obtain a gradient structure blank; the detailed process of the primary rolling is: the blank treated in step S3 is induction heated to 650°C on the surface, rolled with a rolling force of 780kN, with a pass reduction of 15%, and rolled in 4 passes; the detailed process of the core rolling is: the blank after the primary rolling is heated to 600°C as a whole, rolled with a rolling force of 250kN, with a pass reduction of 5.0%, and rolled in 4 passes. S5. Partition annealing to stabilize the gradient grain boundary: the blank treated in step S4 is subjected to surface annealing and core annealing in sequence, and finally a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness is obtained. The detailed process of surface annealing is: using laser selective heating, the heating power density is 4.0W / mm², the spot diameter is 2.0mm, the surface area is heated to 650℃, after keeping warm for 30min, argon gas injection cooling is used, and the cooling rate is 40℃ / s. The detailed process of core annealing is: placing the blank in a resistance furnace, heating to 480℃ at a heating rate of 5.0℃ / min, keeping warm for 90min, and cooling to room temperature at a cooling rate of 2.0℃ / min.
[0047] A low hydrogen embrittlement and high toughness sponge zirconium-based composite material in this embodiment, the sponge zirconium-based composite material is composed of nano ZrC and Zr matrix; the volume ratio of nano ZrC to Zr matrix is 8.0:92.0; the average diameter of nano ZrC is 60nm; nano ZrC is in-situ self-generated by sponge zirconium powder and nano carbon black at high temperature; the sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside; the thickness of the surface region is 35μm; the small-angle grain boundaries in the surface region account for 82.3%; the large-angle grain boundaries account for 14.2%; the twin boundaries account for 0.5%; the thickness of the transition region is 51μm; the small-angle grain boundaries in the transition region account for 25.7%; the large-angle grain boundaries account for 59.7%; the twin boundaries account for 6.0%; the small-angle grain boundaries in the core account for 6.5%, the large-angle grain boundaries account for 71.8%; the twin boundaries account for 13.4%.
[0048] Depend on Figure 1It can be seen that the sponge zirconium-based composite material prepared in Example 1 of the present invention has an obvious gradient structure, and its microstructure is divided into a surface region, a transition region and a core region from the outside to the inside, wherein the surface region presents a large number of fine grains, proving that the present invention successfully constructs a surface fine-grained structure through a specific process. In addition, Figure 2 The electron backscatter diffraction (EBSD) analysis results further verified that the surface area contained a large number of small-angle grain boundaries, indicating that the grains in this area had obvious misorientation accumulation during the plastic deformation process. The formation of this structural feature shows that the surface mechanical grinding and subsequent gradient grain boundary control process adopted by the present invention effectively promoted the formation of surface nanocrystalline structure, providing important support for improving the strength, toughness and hydrogen embrittlement resistance of the material.
[0049] Example 2
[0050] A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material comprises the following steps:
[0051] S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder; the detailed process is: Sponge zirconium powder and carbon black are mixed in a mass ratio of 97.3:2.7, the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is 10.6:1, the rotation speed is 315rpm, and the ball milling time is 27h to obtain Zr-C composite powder.
[0052] S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano ZrC dispersion-reinforced zirconium-based composite material blank is synthesized in situ; the detailed process is as follows: the Zr-C composite powder obtained in step S1 is loaded into a soft steel bag, and after evacuating to ≤5×10⁻³Pa, it is sealed by electron beam sealing welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1215°C at a heating rate of 12°C / min, a pressure of 129MPa is applied, and the temperature and pressure are maintained for 198min. After the reaction is completed, the bag is cooled to room temperature at a cooling rate of 7.8°C / min.
[0053] S3. Surface mechanical grinding treatment: The green body of step S2 is subjected to surface mechanical grinding treatment to form a surface nanocrystalline structure; the detailed process is: the green body obtained in step S2 is placed in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 22kHz, the amplitude to 53μm, the processing time to 53min, and adopting argon jet cooling during the treatment process. After the treatment is completed, argon jet cooling is adopted, and the cooling rate is 43℃ / s.
[0054] S4. Multi-stage warm rolling and grain boundary gradient control, the billet treated in step S3 is subjected to initial rolling and core rolling in sequence to obtain a gradient structure billet; the detailed process of the initial rolling is: the billet surface is induction heated to 665°C after the treatment in step S3, and rolling is performed with a rolling force of 786 kN, a pass reduction of 17%, and rolling is performed in 5 passes; the detailed process of the core rolling is: the billet after the initial rolling is heated as a whole to 615°C, and rolled with a rolling force of 265 kN, a pass reduction of 5.9%, and rolling is performed in 5 passes.
[0055] S5. Partition annealing to stabilize gradient grain boundaries: The blank treated in step S4 is subjected to surface annealing and core annealing in sequence, and finally a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness is obtained. The detailed process of surface annealing is as follows: laser selective heating is used, the heating power density is 4.3W / mm², the spot diameter is 2.6mm, the surface area is heated to 653℃, after keeping warm for 35min, argon gas injection cooling is used, and the cooling rate is 43℃ / s. The detailed process of core annealing is as follows: the blank is placed in a resistance furnace, heated to 483℃ at a heating rate of 5.9℃ / min, after keeping warm for 99min, it is cooled to room temperature at a cooling rate of 2.9℃ / min.
[0056] A low hydrogen embrittlement and high toughness sponge zirconium-based composite material in this embodiment, the sponge zirconium-based composite material is composed of nano ZrC and Zr matrix; the volume ratio of nano ZrC to Zr matrix is 7.3:92.7; the average diameter of nano ZrC is 46.0nm; nano ZrC is in-situ self-generated by sponge zirconium powder and nano carbon black at high temperature; the sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside; the thickness of the surface region is 45μm; the small-angle grain boundaries in the surface region account for 84.5%; the large-angle grain boundaries account for 12.0%; the twin boundaries account for 0.8%; the thickness of the transition region is 85μm; the small-angle grain boundaries in the transition region account for 28.0%; the large-angle grain boundaries account for 60.0%; the twin boundaries account for 6.5%; the small-angle grain boundaries in the core account for 7.5%, the large-angle grain boundaries account for 74.0%; the twin boundaries account for 15.5%.
[0057] Example 3
[0058] A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material comprises the following steps:
[0059] S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder; the detailed process is: Sponge zirconium powder and carbon black are mixed in a mass ratio of 97.6:2.4, the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is 11.2:1, the rotation speed is 330rpm, and the ball milling time is 28h to obtain Zr-C composite powder.
[0060] S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano-ZrC dispersion-reinforced zirconium-based composite material blank is synthesized in situ; the detailed process is as follows: the Zr-C composite powder obtained in step S1 is loaded into a soft steel bag, and after evacuating to ≤5×10⁻³Pa, it is sealed by electron beam sealing welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1230°C at a heating rate of 13°C / min, a pressure of 138MPa is applied, and the temperature and pressure are maintained for 216min. After the reaction is completed, the bag is cooled to room temperature at a cooling rate of 9.6°C / min.
[0061] S3. Surface mechanical grinding treatment: The green body of step S2 is subjected to surface mechanical grinding treatment to form a surface nanocrystalline structure; the detailed process is: the green body obtained in step S2 is placed in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 23kHz, the amplitude to 56μm, the processing time to 56min, and adopting argon jet cooling during the treatment process. After the treatment is completed, argon jet cooling is adopted, and the cooling rate is 46℃ / s.
[0062] S4. Multi-stage warm rolling and grain boundary gradient control, the billet treated in step S3 is subjected to initial rolling and core rolling in sequence to obtain a gradient structure billet; the detailed process of the initial rolling is: the billet surface is induction heated to 680°C after the treatment in step S3, and rolling is performed with a rolling force of 792 kN, a pass reduction of 18%, and rolling is performed in 5 passes; the detailed process of the core rolling is: the billet after the initial rolling is heated as a whole to 630°C, and rolled with a rolling force of 280 kN, a pass reduction of 6.8%, and rolling is performed in 5 passes.
[0063] S5. Partition annealing to stabilize gradient grain boundaries: The blank treated in step S4 is subjected to surface annealing and core annealing in sequence to finally obtain a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness. The detailed process of surface annealing is: laser selective heating is used with a heating power density of 4.6W / mm² and a spot diameter of 3.2mm to heat the surface area to 656°C. After keeping the temperature for 39 minutes, argon gas injection cooling is used with a cooling rate of 46°C / s. The detailed process of core annealing is: the blank is placed in a resistance furnace and heated to 486°C at a heating rate of 6.8°C / min. After keeping the temperature for 108 minutes, it is cooled to room temperature at a cooling rate of 3.8°C / min.
[0064] A low hydrogen embrittlement and high toughness sponge zirconium-based composite material in this embodiment, the sponge zirconium-based composite material is composed of nano ZrC and Zr matrix; the volume ratio of nano ZrC to Zr matrix is 6.5:93.5; the average diameter of nano ZrC is 27.5nm; nano ZrC is in-situ self-generated by sponge zirconium powder and nano carbon black at high temperature; the sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside; the thickness of the surface region is 55μm; the small-angle grain boundaries in the surface region account for 86.0%; the large-angle grain boundaries account for 11.5%; the twin boundaries account for 0.5%; the thickness of the transition region is 110μm; the small-angle grain boundaries in the transition region account for 30.0%; the large-angle grain boundaries account for 62.0%; the twin boundaries account for 6.5%; the small-angle grain boundaries in the core account for 9.7%, the large-angle grain boundaries account for 77.5%; the twin boundaries account for 12.8%.
[0065] Example 4
[0066] A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material comprises the following steps:
[0067] S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder; the detailed process is: Sponge zirconium powder and carbon black are mixed in a mass ratio of 98.0:2.0, the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is 12.0:1, the rotation speed is 350rpm, and the ball milling time is 30h to obtain Zr-C composite powder.
[0068] S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano ZrC dispersion-reinforced zirconium-based composite material blank is synthesized in situ; the detailed process is as follows: the Zr-C composite powder obtained in step S1 is loaded into a soft steel bag, evacuated to ≤5×10⁻³Pa, and then sealed by electron beam welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1250°C at a heating rate of 15°C / min, a pressure of 150MPa is applied, and the temperature is maintained at this temperature for 240min. After the reaction is completed, the temperature is cooled to room temperature at a cooling rate of 12.0°C / min.
[0069] S3. Surface mechanical grinding treatment: The green body of step S2 is subjected to surface mechanical grinding treatment to form a surface nanocrystalline structure; the detailed process is: the green body obtained in step S2 is placed in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 25kHz, the amplitude to 60μm, the processing time to 60min, and argon jet cooling during the treatment process. After the treatment is completed, argon jet cooling is used, and the cooling rate is 50℃ / s.
[0070] S4. Multi-stage warm rolling and grain boundary gradient control, the billet treated in step S3 is subjected to initial rolling and core rolling in sequence to obtain a gradient structure billet; the detailed process of the initial rolling is: the billet surface is induction heated to 700°C after the treatment in step S3, and rolling is performed with a rolling force of 800 kN, a pass reduction of 20%, and 6 passes; the detailed process of the core rolling is: the billet after the initial rolling is heated as a whole to 650°C, and rolled with a rolling force of 300 kN, a pass reduction of 8.0%, and 6 passes.
[0071] S5. Partition annealing to stabilize gradient grain boundaries: The blank treated in step S4 is subjected to surface annealing and core annealing in sequence to finally obtain a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness. The detailed process of surface annealing is: laser selective heating is used with a heating power density of 5.0W / mm² and a spot diameter of 4.0mm to heat the surface area to 660°C. After keeping the temperature for 45 minutes, argon gas injection cooling is used at a cooling rate of 50°C / s. The detailed process of core annealing is: the blank is placed in a resistance furnace, heated to 490°C at a heating rate of 8.0°C / min, kept at the temperature for 120 minutes, and then cooled to room temperature at a cooling rate of 5.0°C / min.
[0072] A low hydrogen embrittlement and high toughness sponge zirconium-based composite material in this embodiment, the sponge zirconium-based composite material is composed of nano ZrC and Zr matrix; the volume ratio of nano ZrC to Zr matrix is 4.5:95.5; the average diameter of nano ZrC is 10.0nm; nano ZrC is in-situ self-generated by sponge zirconium powder and nano carbon black at high temperature; the sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside; the thickness of the surface region is 68μm; the small-angle grain boundaries in the surface region account for 83.0%; the large-angle grain boundaries account for 11.7%; the twin boundaries account for 0.5%; the thickness of the transition region is 145μm; the small-angle grain boundaries in the transition region account for 32.5%; the large-angle grain boundaries account for 63.0%; the twin boundaries account for 7.0%; the small-angle grain boundaries in the core account for 10.5%, the large-angle grain boundaries account for 78.8%; the twin boundaries account for 18.7%.
[0073] Comparative Example 1
[0074] The method is basically the same as Example 1, except that the zirconium sponge powder and the nano carbon black are mixed in a mass ratio of 96.5:3.5.
[0075] Comparative Example 2
[0076] The process is basically the same as Example 1, except that the ball milling time is set to 20 h.
[0077] Comparative Example 3
[0078] The process is basically the same as Example 1, except that the ball milling time is set to 35 h.
[0079] Comparative Example 4
[0080] It is basically the same as Example 1, except that the hot isostatic pressing temperature is set to 1180°C.
[0081] Comparative Example 5
[0082] It is basically the same as Example 1, except that the surface mechanical grinding vibration frequency is set to 18 kHz.
[0083] Comparative Example 6
[0084] It is basically the same as Example 1, except that the initial rolling temperature is set to 620°C.
[0085] Comparative Example 7
[0086] It is basically the same as Example 1, except that the cooling rate after surface annealing is set to 30°C / s.
[0087] Comparative Example 8
[0088] It is basically the same as Example 1, except that the core annealing temperature is set to 500°C.
[0089] Performance Test:
[0090] Tensile performance test: The composite material was subjected to tensile test using an electronic universal testing machine to test its yield strength, tensile strength and elongation. The samples were prepared according to ASTM E8 standard, and the test temperature was set at room temperature and 400°C to simulate the mechanical properties under different service environments. The strength and plasticity of the composite material were evaluated by stress-strain curve, and the crack propagation mechanism was observed in combination with fracture analysis.
[0091] Impact toughness test: The composite material was tested for impact toughness using a Charpy impact tester at room temperature and low temperature (-196°C, liquid nitrogen environment). The impact specimens were prepared according to ASTM E23 standards, and the brittle fracture characteristics of the material were evaluated by fracture morphology analysis. This experiment can be used to evaluate the effect of nano ZrC on relative toughness.
[0092] Hydrogen embrittlement sensitivity test: This test program evaluates hydrogen embrittlement of metal materials according to ASTM G142-98 standard, uses high-pressure hydrogen environment (0.1MPa, 1MPa, 5MPa) for testing, and ensures that the test temperature is constant (such as 300℃, 600℃). The test method uses slow strain rate tensile (SSRT), and the strain rate is set to 10⁻ 6 ~10⁻ 5 s⁻¹, which is in line with the recommended range of the standard. After the tensile test, the yield strength, tensile strength and elongation after fracture were measured, and the mechanical properties were compared with those of the non-hydrogen-filled specimens. After the test, the fracture morphology was observed using a scanning electron microscope (SEM) to analyze the hydrogen embrittlement fracture characteristics, such as intergranular fracture and quasi-cleavage fracture, to evaluate the hydrogen embrittlement sensitivity of the material.
[0093] Hydrogen permeation test: The hydrogen permeability of the material is determined by the Sievert method, and the test temperature range is 200~600℃ to simulate the application environment of the nuclear industry. By measuring the hydrogen permeation rate at different temperatures, the influence of the surface nanocrystalline structure on the hydrogen diffusion behavior is analyzed, and the hydrogen barrier ability of the material is verified.
[0094] The properties of the zirconium sponge-based composite materials of Examples 1 to 4 and Comparative Examples 1 to 7 are summarized in Table 1.
[0095] Table 1 Performance of zirconium sponge-based composite materials of Examples 1 to 4 and Comparative Examples 1 to 7
[0096] The mechanical properties and hydrogen embrittlement resistance of the material are significantly affected by multiple process parameters. First, the raw material ratio directly determines the uniformity of the distribution of the nano-reinforced phase. If the carbon content is too high, the particle size may increase, reducing the ductility and impact toughness of the material. The mechanical alloying process is also a key factor. Too short ball milling time will lead to uneven powder mixing, affecting the density of subsequent sintering, while too long ball milling time may cause powder agglomeration and weaken the overall mechanical properties of the material. The hot isostatic pressing temperature affects the in-situ synthesis degree of ZrC. Low temperature may increase the porosity and reduce the strength and toughness of the material. Surface mechanical grinding improves the surface strengthening effect of the material by refining the surface grains. If the vibration frequency is too low, the nanocrystalline structure may not be refined enough, reducing the strengthening degree of the material. The warm rolling process affects the stability of the gradient grain boundary. Low rolling temperature may lead to uneven deformation, which in turn affects the comprehensive mechanical properties of the material. Annealing treatment is also an important link in determining the final performance. Too low cooling rate will cause the nanograins to grow and reduce the surface strengthening effect. Properly increasing the core annealing temperature can optimize the stress state of the material, thereby improving some mechanical properties. In summary, factors such as raw material ratio, ball milling time, hot isostatic pressing temperature, and surface treatment parameters have an important influence on the hydrogen embrittlement sensitivity of the material. Reasonable optimization of various process parameters can ensure the excellent mechanical properties of the material while improving its resistance to hydrogen embrittlement and achieving the best overall performance.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material, characterized in that: The following steps are involved: S1. Raw material pretreatment and mechanical alloying: Sponge zirconium powder and nano carbon black are mixed as raw materials and then mechanically alloyed to obtain Zr-C composite powder; S2. Hot isostatic pressing densification and in-situ synthesis: The Zr-C composite powder obtained in step S1 is subjected to hot isostatic pressing densification, and a nano-ZrC dispersion-reinforced zirconium-based composite body is synthesized in situ; S3. Surface mechanical grinding: The body of step S2 is subjected to surface mechanical grinding to form a surface nanocrystalline structure; S4. Multi-stage warm rolling and grain boundary gradient control: The blank treated in step S3 is subjected to primary rolling and core rolling in sequence to obtain a gradient structure blank; S5. Partition annealing to stabilize the gradient grain boundary: The green body treated in step S4 is subjected to surface annealing and core annealing in sequence to finally obtain a sponge zirconium-based composite material with low hydrogen embrittlement and high toughness.
2. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of step S1 is: sponge zirconium powder and carbon black are mixed in a mass ratio of (97.0-98.0): (2.0-3.0), the mixed powder is placed in a high-energy planetary ball mill, and mechanical alloying is performed under argon protection. The ball milling parameters are set as follows: the ball-to-material ratio is (10.0-12.0):1, the rotation speed is 300-350 rpm, and the ball milling time is 25-30 hours to obtain Zr-C composite powder.
3. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of step S2 is as follows: the Zr-C composite powder obtained in step S1 is loaded into a mild steel bag, and after evacuating to ≤5×10⁻³Pa, it is sealed by electron beam sealing welding, and the sealed powder bag is placed in a hot isostatic pressing furnace, heated to 1200~1250°C at a heating rate of 10~15°C / min, a pressure of 120~150MPa is applied, and the temperature and pressure are maintained for 180~240min. After the reaction is completed, the bag is cooled to room temperature at a cooling rate of 6.0~12.0°C / min.
4. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of step S3 is as follows: placing the green body obtained in step S2 in an ultrasonic surface mechanical grinding device, using WC-Co grinding balls, setting the vibration frequency to 20-25kHz, the amplitude to 50-60μm, the processing time to 50-60min, adopting argon gas jet cooling during the processing, and after the processing is completed, adopting argon gas jet cooling, and the cooling rate is 40-50℃ / s.
5. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of the initial rolling in step S4 is as follows: the surface of the billet treated in step S3 is induction heated to 650-700° C., and rolling is performed with a rolling force of 780-800 kN, a pass reduction of 15-20%, and 4-6 passes.
6. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 5, characterized in that: The detailed process of the core rolling in step S4 is as follows: heating the blank after the initial rolling to 600-650° C. as a whole, rolling with a rolling force of 250-300 kN, a pass reduction of 5.0-8.0%, and rolling in 4-6 passes.
7. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of the surface annealing in step S5 is: using laser selective heating, the heating power density is 4.0~5.0W / mm², the spot diameter is 2.0~4.0mm, the surface area is heated to 650~660℃, after keeping warm for 30~45min, argon gas injection cooling is used, and the cooling rate is 40~50℃ / s.
8. The method for preparing a low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 1, characterized in that: The detailed process of the core annealing in step S5 is as follows: placing the blank in a resistance furnace, heating it to 480-490°C at a heating rate of 5.0-8.0°C / min, keeping it at that temperature for 90-120 minutes, and then cooling it to room temperature at a cooling rate of 2.0-5.0°C / min.
9. A low hydrogen embrittlement and high toughness sponge zirconium-based composite material, characterized in that: The zirconium sponge-based composite material is prepared by the preparation method according to any one of claims 1 to 8; The sponge zirconium-based composite material is composed of nano ZrC and a Zr matrix; The volume ratio of the nano ZrC and the Zr matrix is (4.5~8.0): (92.0~95.5); The average diameter of the nano ZrC is 10.0-60.0 nm; The nano ZrC is in-situ self-generated from sponge zirconium powder and nano carbon black at high temperature.
10. A low hydrogen embrittlement and high toughness sponge zirconium-based composite material according to claim 9, characterized in that: The sponge zirconium-based composite material is composed of a surface region, a transition region, and a core region from the outside to the inside; The thickness of the surface region is 35-70 μm; the small-angle grain boundaries in the surface region account for 82.3-88.7%; the large-angle grain boundaries account for 11.7-15.9%; and the twin boundaries account for 0.4%-1.0%; The thickness of the transition region is 50-150 μm; the small-angle grain boundaries in the transition region account for 25.7-34.7%; the large-angle grain boundaries account for 59.7-67.3%; and the twin boundaries account for 5.1-7.5%; The small-angle grain boundaries in the core account for 6.5-10.5%, the large-angle grain boundaries account for 71.8-78.8%; and the twin boundaries account for 13.4-19.0%.
Citation Information
Patent Citations
Zirconium alloy for fuel assembly, manufacturing method of zirconium alloy and cladding tube of fuel assembly
CN113201666A
Zirconium-aluminum-silicon-carbon-silicon carbide composite material and preparation method thereof
CN101824576A
In-situ synthesized zirconium-based composite material reinforced by using zirconium carbide particles, and preparation method thereof
CN102443719A
Zr-based alloy surface gradient ZrC coating and preparation method thereof
CN113136541A